O risco de desenvolvimento e a responsabilidade civil - Breviglieri, Etiene Maria Bosco (2013)
This study presents a comparative analysis of the risk of development as exclusion of liability in different jurisdictions. For this purpose, includes the main concepts and ideas advocated by the sociologist Ulrich Beck has called that today's society as "risk society". Within this paper presents a legal analysis of the text of the European Directive n. 374 of 1985 on the effects of their adoption by different member states of the European Community as a starting point for further reflections on the possible inclusion of the risk of development as excluding liability in our civil or consumerist law. It also includes reflections of new technologies and their interaction with the risk of development in order to confirm their applicability or not with nanotechnology and genetic manipulation. Due to the continued appearance of innovative technologies whose risks cannot be predicted and calculated the work points to the use of the principle of precaution and prevention to control risks from new technologies. Finally, it also brings two proposals of lege ferenda that address the risk of development planning in our civil and consumer in promoting the discussing of possibility of additions to the theme of the Civil Code and the Code of Consumer Protection